New Weed Hosts for Tomato Brown Rugose Fruit Virus in Wild Mediterranean Vegetation - Nida’ M. Salem; Motasem Abumuslem; Massimo Turina; Nezar Samarah; Abdullah Sulaiman; Barakat Abu-Irmaileh; Yousra Ata (Plants, 2022)
Tomato brown rugose fruit virus (ToBRFV; genus, Tobamovirus, family, Virgaviridae) was first reported in 2015 infecting tomatoes grown under protected cropping in the Jordan Valley. Since then, ToBRFV has been detected in tomatoes grown in both protected and open fields across Jordan. The increased incidence of ToBRFV prompted this investigation of the potential role of natural weed hosts in the dissemination of ToBRFV. A survey was conducted in the Jordan Valley and highlands to determine possible reservoir hosts of ToBRFV in fields and greenhouse complexes in which tomatoes were grown. Detection of ToBRFV infection was made by double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) and further confirmation by reverse-transcription polymerase chain reaction (RT-PCR), followed by DNA cloning and sequencing, and bioassays. Thirty weed species belonging to twenty-six genera from sixteen families were tested. Twelve species belonging to eight families were infected of which ten species are newly reported hosts for ToBRFV. Seed transmission of ToBRFV in Solanum nigrum was confirmed in a grow-out experiment. To our knowledge, this is the first report of the natural occurrence of ToBRFV on weed hosts. Identification of natural reservoirs of ToBRFV can help to develop management practices focused on weed plant species to prevent ToBRFV transmission. The extent to which ToBRFV survives in diverse alternate weed host species outside tomato growing seasons in different world regions requires further research in order to establish the risk associated with the possible contribution of weeds as a reservoir for primary infections in tomato crops.